2010
DOI: 10.1128/iai.00456-10
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 (IL-7) Treatment Accelerates Neutrophil Recruitment through γδ T-Cell IL-17 Production in a Murine Model of Sepsis

Abstract: The sepsis syndrome represents an improper immune response to infection and is associated with unacceptably high rates of mortality and morbidity. The interactions between T cells and the innate immune system while combating sepsis are poorly understood. In this report, we observed that treatment with the potent, antiapoptotic cytokine interleukin-7 (IL-7) accelerated neutrophil recruitment and improved bacterial clearance. We first determined that T cells were necessary for the previously observed IL-7-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 63 publications
5
114
1
1
Order By: Relevance
“…Recently, this paradigm was elegantly corroborated in mice subjected to sepsis and rescued by administration of IL-7, an anti-apoptotic cytokine essential for lymphocyte survival and expansion [44,45]. As mentioned previously, studies in human volunteers challenged with endotoxin revealed early repression of gene programs related to adaptive immunity [22].…”
Section: Genome-level Understanding Of Sepsismentioning
confidence: 89%
“…Recently, this paradigm was elegantly corroborated in mice subjected to sepsis and rescued by administration of IL-7, an anti-apoptotic cytokine essential for lymphocyte survival and expansion [44,45]. As mentioned previously, studies in human volunteers challenged with endotoxin revealed early repression of gene programs related to adaptive immunity [22].…”
Section: Genome-level Understanding Of Sepsismentioning
confidence: 89%
“…Recently, it was reported that gdT cells have been implicated as the major producer of IL-17 during sepsis (30). Furthermore, treatment of IL-7, which stabilizes the number of T cell and function, accelerates neutrophil recruitment through gd T cell IL-17 production in a murine model of sepsis (31). On the basis of these two reports, gd T cell could be involved in production of IL-17A in late phase after I/R.…”
Section: Role Of Il-17a In Neutrophil Recruitment After I/rmentioning
confidence: 95%
“…Recombinant human IL-7 (rhIL-7) therapy has been evaluated in preclinical sepsis models, and data suggest benefi cial effects, including increased cytokine production capacity, T-cell proliferation, prevention of lymphocyte apoptosis, and improved survival. [65][66][67][68][69][70] Ex vivo treatment of lymphocytes from patients with sepsis with IL-7 signifi cantly improved T-cell proliferation, up-regulation of anti-apoptotic proteins, and IFN-γ production capacity. 63 Whereas rhIL-7 is currently being evaluated in patients with chronic viral infection and cancer, to date it remains unstudied in vivo in the setting of critical illness.…”
Section: Adaptive Immune Stimulating Agentsmentioning
confidence: 99%